Seasonal Economic Dynamics in East Nusa Tenggara: A Comparative Study of Rote Ndao Regency and Kupang Regency on Socio-Economic Impacts, Challenges, and Solutions - Marthen Lona (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the differences in seasonal economic dynamics between Rote Ndao Regency and Kupang Regency, East Nusa Tenggara, focusing on socio-economic impacts, challenges faced, and proposed solutions. The research employs a comparative approach using mixed methods, involving in-depth interviews, quantitative surveys, and secondary data analysis from the Central Bureau of Statistics. Such a mixed methodological design allows for a more holistic understanding of how seasonal economic variations affect communities in two regions that, while geographically close, have distinct socio-economic characteristics. The findings reveal significant differences in seasonal economic patterns influenced by geographical factors, market access, and livelihood diversification. In Rote Ndao, the economy is largely dependent on agriculture, fisheries, and small-scale trade, which are highly sensitive to weather patterns and seasonal fluctuations. Conversely, Kupang Regency, as a more urbanized and accessible area, demonstrates relatively greater resilience due to diversified economic activities, stronger infrastructure, and better market connectivity. Socio-economic impacts of seasonal changes include income fluctuations, instability in employment opportunities, and disparities in community welfare levels. Households in Rote Ndao often face more severe income instability during off-seasons, leading to higher vulnerability to poverty, while Kupang communities are comparatively more adaptive due to broader livelihood options. The main challenges identified across both regions include limited infrastructure, low workforce skills, and restricted access to financing, with Rote Ndao experiencing greater intensity of these barriers. Limited roads and transportation systems constrain market access, while low educational attainment reduces workforce competitiveness. Furthermore, weak financial inclusion hampers investment in productive sectors. Proposed solutions include improving transportation infrastructure to enhance connectivity and reduce logistic costs, developing creative and sustainable economies based on local potential such as marine resources and tourism, and strengthening human resource capacity through vocational training and education. By addressing these structural constraints, both regions may reduce seasonal vulnerabilities and foster inclusive and sustainable economic growth.